The modified WHO class is associated with maternal complications in women with congenital heart disease - Jonsson, Sara; Johansson, Bengt; Wikström, Anna Karin; Dahlqvist, Jenny Alenius; Christersson, Christina; Sörensson, Peder; Trzebiatowska-Krzynska, Aleksandra; Dellborg, Mikael; Thilén, Ulf; Sundström-Poromaa, Inger; Bay, Annika (European Heart Journal Open, 2025)
Aims With a growing population of women with congenital heart disease (CHD), pregnancies in this group are expected to increase. However, pregnancy in women with CHD is associated with increased adverse outcomes for both mother and child. The aim of this study was to evaluate pregnancy and foetal complications in women with CHD and to test their association with the modified WHO (mWHO) classification. Methods Using two national registers, the national register for CHD and the Pregnancy Register, primiparous women giving birth and results between 2014 and 2019 were identified. Women with CHD, n = 829, and women without CHD, n = 4137, were matched by birth year and municipality in a ∼1:5 ratio. The women with CHD were classified according to the mWHO criteria. Caesarean deliveries (25.7 vs. 17.2%, P < 0.001), preterm delivery (10.3 vs. 6.4%, P < 0.001), and preeclampsia (6.2 vs. 4.1%, P = 0.007) were more common in women with CHD compared with controls. Using logistic regression, there was an association between high mWHO class (mWHO III, IV) and caesarean section [odds ratio (OR) 3.4, 95% confidence interval (CI) 1.8–6.7], preterm birth (<37 weeks) (OR 8.3, 95% CI 4.1–17.1), and preeclampsia (OR 3.8, 95% CI 1.5–9.9). Conclusion Pregnancy complications are more common in women with CHD. In women with CHD, the mWHO classification is associated with maternal complications and preterm birth. Thus, large national register data corroborate the advice provided in current guidelines, and the mWHO class is deemed a valuable risk stratification tool in women with CHD.
Publisher Copyright: © The Author(s) 2025.
Keywords: Adult congenital heart disease; mWHO; Pregnancy